2017
DOI: 10.1123/ijsnem.2016-0251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Nitrate Supplementation on Swimming Performance in Trained Swimmers

Abstract: Nitrate supplementation appears to be most ergogenic when oxygen availability is restricted and subsequently may be particularly beneficial for swimming performance due to the breathhold element of this sport. This represents the first investigation of nitrate supplementation and swimming time-trial (TT) performance.In a randomised double-blind repeated-measures crossover study, ten (5male, 5female) trained swimmers ingested 140ml nitrate-rich (~12.5mmol nitrate) or nitrate-depleted (~0.01mmol nitrate) beetroo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
6
19
2
Order By: Relevance
“…The variation at the final time of the 10-km running performance test between the BRJ and PLA conditions was 0.9 ± 2.1 minutes (P = 0.130), indicating an improvement of 1.9 ± 4.2% on running performance with a "trivial" effect size. Our results are in agreement with D r a f t previous studies that evaluated the effects of BRJ on long duration endurance performance (Shannon et al, 2017;Wilkerson et al, 2012) and with a literature review and meta-analysis that found a "trivial" but not significant effect in favor of dietary supplementation of NO 3 -, which can be translated into improvement of 0.8% in the final performance (McMahon et al, 2016). Although the result of the present study may seem small in the competitive environment in which athletes have very similar levels of performances, the improvement of 0.5 to 1.5% is considered sufficient to make a difference between the competitors (Dominguéz et al, 2018;Paton and Hopkins, 2006) as well as the final result of the performance.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The variation at the final time of the 10-km running performance test between the BRJ and PLA conditions was 0.9 ± 2.1 minutes (P = 0.130), indicating an improvement of 1.9 ± 4.2% on running performance with a "trivial" effect size. Our results are in agreement with D r a f t previous studies that evaluated the effects of BRJ on long duration endurance performance (Shannon et al, 2017;Wilkerson et al, 2012) and with a literature review and meta-analysis that found a "trivial" but not significant effect in favor of dietary supplementation of NO 3 -, which can be translated into improvement of 0.8% in the final performance (McMahon et al, 2016). Although the result of the present study may seem small in the competitive environment in which athletes have very similar levels of performances, the improvement of 0.5 to 1.5% is considered sufficient to make a difference between the competitors (Dominguéz et al, 2018;Paton and Hopkins, 2006) as well as the final result of the performance.…”
Section: Resultssupporting
confidence: 93%
“…Boorsma et al (2014) did not find improvement in the completion time of 1500 m after the acute or chronic BRJ supplementation in trained runners despite the fact that two individuals were identified as high responders. On the contrary, in another study using the same distance and a similar sample, acute supplementation with BRJ was able to reduce the test time in supplemented individuals (Shannon et al 2017). At longer distances (5-km), with moderately trained individuals, acute supplementation with 500 mg NO 3 -, despite having a tendency to increase the mean final velocity of the test and a statistically significant increase of 5 % of velocity in the last third of the test with reduction of RPE in the supplemented group, did not find statistical differences in the time of conclusion of the test (Murphy et al, 2012).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Furthermore in healthy trained male and female apnoeists, one single shot of BRJ did not show physiological improvements in heart rate for VO 2 that indicate a beneficial effect of BRJ for free divers (Barlow et al 2018). Also, no beneficial effects on short distance swimming performance and under water phases in a time trial were found in a study performed in well trained swimmers (Lowings et al 2017). Effects of the consumption of a single dose of nitrate-rich BRJ on muscular function or training adaptations here seem beneficial; however, this is not applicable for apnoeists and swimmers.…”
Section: Effects Of a Single Dose Brj Supplementation In Relation To mentioning
confidence: 84%